2005
DOI: 10.1016/j.jviromet.2004.11.012
|View full text |Cite
|
Sign up to set email alerts
|

A mRNA PCR for the diagnosis of feline infectious peritonitis

Abstract: A reverse transcriptase polymerase chain reaction (RT-PCR) for the detection of feline coronavirus (FCoV) messenger RNA in peripheral blood mononuclear cells (PBMCs) is described. The assay is evaluated as a diagnostic test for feline infectious peritonitis (FIP). It is based on a well-documented key event in the development of FIP: the replication of virulent FCoV mutants in monocytes/macrophages. To detect most feline coronavirus field strains, the test was designed to amplify subgenomic mRNA of the highly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 25 publications
5
97
2
5
Order By: Relevance
“…22 In a study conducted in Austria, type I was found to be present in 62% of the cats studied. 25 28 The aim of the present investigation was to evaluate the prevalence of FCoVspecific antibodies in the sera of cats from catteries, community shelters, or households by using the virus neutralization (VN) test and then comparing its results with those of IFAT and ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…22 In a study conducted in Austria, type I was found to be present in 62% of the cats studied. 25 28 The aim of the present investigation was to evaluate the prevalence of FCoVspecific antibodies in the sera of cats from catteries, community shelters, or households by using the virus neutralization (VN) test and then comparing its results with those of IFAT and ELISA.…”
Section: Introductionmentioning
confidence: 99%
“…Viral RNA has, however, also been detected by RT-PCR in blood and some (haemolymphatic) tissues of infected animals (Gunn- Moore et al, 1998;Herrewegh et al, 1995aHerrewegh et al, , 1997Kipar et al, 2006a, b;Meli et al, 2004;Simons et al, 2005). The significance of this apparent viraemia is still poorly understood.…”
mentioning
confidence: 99%
“…Whilst cells of the monocyte lineage are the prime targets of FIPV, these cells are poorly susceptible to FECV and support FECV replication and spread only very inefficiently, at least in vitro Stoddart & Scott, 1989). Studies aimed at detecting FCoV replication, by using an RT-PCR designed specifically to identify viral mRNA, suggest this to also be the case in vivo (Simons et al, 2005). Actually, viral mRNA or infected cells were not observed in organs other than the intestinal tract.…”
mentioning
confidence: 99%
“…A reverse transcriptase (RT)-PCR was performed in order to detect RNA of FCoV in the blood and brain tissue samples as described previously by Simons et al [14] .…”
Section: Case Historymentioning
confidence: 99%